2023
DOI: 10.1093/femsml/uqad032
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic effects of short-chain fatty acids from the large intestine on host cells

Abstract: Adult humans harbor at least as many microbial cells as eukaryotic ones. The largest compartment of this diverse microbial population, the gut microbiota, encompasses the collection of bacteria, archaea, viruses, and eukaryotic organisms that populate the gastrointestinal tract, and represents a complex and dynamic ecosystem that has been increasingly implicated in health and disease. The gut microbiota carries ∼100-to-150-times more genes than the human genome and is intimately involved in development, homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 297 publications
0
5
0
Order By: Relevance
“…In this regard, behavioral management therapy, cognitive behavioral therapy, speech language therapy, social skills training, and physical and nutritional therapies, as well treatments with medications for the alleviation of some symptoms, are common interventions [181]. The latter include the use of SSRI and tricyclic antidepressants, psychoactive or antipsychotic medications, stimulants, anxiolytics, and anticonvulsants [181,192]. Moreover, because oxidative stress, inflammation, and mitochondrial dysfunction are common pathophysiological mechanisms of ASD, drugs targeting these factors are being advocated [181].…”
Section: Treatment Modalities For Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, behavioral management therapy, cognitive behavioral therapy, speech language therapy, social skills training, and physical and nutritional therapies, as well treatments with medications for the alleviation of some symptoms, are common interventions [181]. The latter include the use of SSRI and tricyclic antidepressants, psychoactive or antipsychotic medications, stimulants, anxiolytics, and anticonvulsants [181,192]. Moreover, because oxidative stress, inflammation, and mitochondrial dysfunction are common pathophysiological mechanisms of ASD, drugs targeting these factors are being advocated [181].…”
Section: Treatment Modalities For Asdmentioning
confidence: 99%
“…Moreover, because oxidative stress, inflammation, and mitochondrial dysfunction are common pathophysiological mechanisms of ASD, drugs targeting these factors are being advocated [181]. In addition, probiotics, prebiotics, fecal microbiota transplantation, microbiota transfer therapy, antibiotics, and dietary adjustment methods may provide additional reliefs [181,[192][193][194].…”
Section: Treatment Modalities For Asdmentioning
confidence: 99%
“…This study also found that HF/HS feeding altered the methylation signature of histone in the mice. Many other studies have reported modulation of the post-translational modification of histones in colonic cells via microbiota-derived SCFAs, which led to differences in IBS [ 133 ].…”
Section: Relationship Between Environmental Inputs Microorganism-deri...mentioning
confidence: 99%
“…The modification of epigenetic landmarks, such as histone deacetylase and acyltransferase, modulate the host's gene expression. The current understanding and knowledge of epigenetic effects of SCFA on cells of the immune has been recently reviewed [108,109].…”
Section: Short-chain Fatty Acid Productionmentioning
confidence: 99%